The relationship between gender role stress and self esteem in students of faculty of health sciences - Kargin, Maral; Aytop, Sinem; Hazar, Seda; Yuksekol, Ozlem Dogan (Wiley, 2021)
Purpose The aim of this study is to determine the relationship between gender role stress and self-esteem. Design and Methods This descriptive study was conducted with 898 faculty of health sciences nursing students who consent to participate. Results There was a negative correlation in male students between the total scores for gender role stress and the total scores for self-esteem. In women, while there was a negative correlation between age and total scores for gender role stress, there was a positive correlation between age and the total scores for self-esteem. Practice Implications It is suggested that trainings concerning gender roles should be planned for undergraduate classes.
Keywords: gender role stress; self-esteem; university students